Overcoming resistance of targeted EGFR monotherapy by inhibition of STAT3 escape pathway in soft tissue sarcoma - Wang, X.; Goldstein, D.; Crowe, P.; Yang, M.; Garrett, K.; Zeps, Nikolajs; Yang, J. (Impact Journals LLC, 2016)
Although epidermal growth factor receptor (EGFR) is often over-expressed in soft tissue sarcoma (STS), a phase II trial using an EGFR inhibitor gefitinib showed a low response rate. This study identified a new secondary resistance mechanism of gefitinib in STS, and developed new strategies to improve the effectiveness of EGFR inhibition particularly by blocking the STAT3 pathway. We demonstrated that seven STS cell lines of diverse histological origin showed resistance to gefitinib despite blockade of phosphorylated EGFR (pEGFR) and downstream signal transducers (pAKT and pERK) in PI3K/AKT and RAS/ERK pathways. Gefitinib exposure was not associated with decrease in the ratio of pSTAT3/pSTAT1. The relative STAT3 abundance and activation may be responsible for the drug resistance. We therefore hypothesized that the addition of a STAT3 inhibitor could overcome the STAT3 escape pathway. We found that the addition of STAT3 inhibitor S3I-201 to gefitinib achieved synergistic anti-proliferative and pro-apoptotic effects in all three STS cell lines examined. This was confirmed in a fibrosarcoma xenografted mouse model, where the tumours from the combination group (418mm3) were significantly smaller than those from untreated (1032mm3) or single drug (912 and 798mm3) groups. Our findings may have clinical implications for optimising EGFR-targeted therapy in STS.